How to analyze and compare scenarios? : evaluation of scenarios dealing with the future of our energy system, DESERTEC, EU-Roadmap 2050, Greenpeace [r]evolution, world energy outlook & Shell Energy scenarios - Krammer, Stefan (Anchor Academic Pub., 2013)
Hauptbeschreibung Right now, our energy system is highly dependent on fossil sources. This dependency causes two major problems: First, it causes the scarcity of these non-renewable energy sources, and climate change. There are two alternatives to fossil energy sources that are on the one hand, nuclear energy, and on the other hand, renewable energy sources. The process of nuclear energy is fascinating for the energy outcome of one kilogram of uranium equals the stored energy of about 3.000 tons of coal. Nuclear energy can reduce the problems that cause climate change for, the p.